THE ACTIVITY OF BOVINE MILK, COCONUT MILK AND SOYA BEAN MILK ON GROWTH OF ENTAMOEBA HITOLYTICA TROPHOZOITE IN VITRO - Ahmed, Zahra’a (Iraqi Journal of Science, 2024)
Trophozoites of Entamoeba histolytica were isolated from a stool sample, and then cultivated and maintained axenically by using Locke-egg medium (LEM). The effect of supplementation of two different milk sources on the growth and activity of the parasite was investigated. The first source which is an animal (bovine milk) and the second is plant source (coconut & soybean milk). Different concentrations of milk (1, 5, and 10 %) have been added to the Locke-egg medium that is specified to the growth of E. histolytica. The ability of these three types of milk in inhibiting the E. histolytica growth was examined after 24 and 48h of incubation in addition to morphological changes that parasites underwent were observed. The results showed that bovine & soybean milk were active in the inhibition of the growth of E.histolytica trophozoite, and the inhibition rate reaches to 80.7% and 51.3% respectively at the concentration of 1%, after 48h of incubation. But the inhibition rate for coconut milk is less than other types of milk and the inhibition rate reaches to 20% at the concentration of 1%, after 48h of incubation. While the inhibition rate was increased at the concentration 5% and 10%, after 48h of incubation when the milk of bovine and soybean and coconut were supplemented to LEM medium to reach %3.79,%33 , 84.6 % respectively at 5% concentration , while at 10% concentration was reach to %337., %3379, %3.79 respectively.Encystment of E.histolytica has been noticed and morphological changes in the parasite have been observed that led to lyses of parasite which were resulting from the stopped phagocytosis and endosmosis.